تأثير الجوانب المادية على جودة خدمة التأمين الصحي دراسة ميدانية على عملاء شركات التأمين الصحي في الساحل السوري - غدير, باسم; فياض, شادي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف هذا البحث إلى دراسة تأثير الجوانب المادية أو ما يعرف ببعد الملموسية على جودة خدمة التأمين الصحي في الساحل السوري، واختبار اعتداد العملاء بالجوانب الماديّة عند تقييمهم لجودة الخدمة المقدمة لهم، ورضاهم عن هذه الخدمة.اتبع الباحث أسلوب الاستبانة الإحصائية لجمع البيانات حول مشكلة البحث، حيث وجهت الاستبانة إلى عينة من /300/ فرد من عملاء الشركات محل الدراسة، ومن ثم تحليل النتائج عبر البرامج الإحصائية المناسبة.وأظهرت النتائج أنّ درجة جودة الخدمة المقدّمة من قبل شركات التأمين الصحي في الساحل السوري منخفضة بالنسبة لبعد الملموسية، وأن الجوانب المادية تؤثر بشكل إيجابي على جودة هذه الخدمة، بحيث نالت التوقعات عن الجوانب المادية التأثير الأكبر، في حين كان لإدراك العملاء لهذه الجوانب تأثيراً موجباً ولكنه غير كافي؛ بدون مقابلة التوقعات أو الزيادة عنها. وقدم الباحث مجموعة من المقترحات والتوصيات التي تهدف إلى مساعدة الشركات محل الدراسة في تحسين إدراك العملاء للجوانب المادية المقدمة لهم، كمواكبة التطور التقني والتكنولوجي المرافق لتقديم الخدمة، والاهتمام بالمظهر الخارجي والداخلي للشركة، بالإضافة إلى ضرورة تبني الإدارة لجودة الخدمة كإستراتيجية للتميّز والمنافسة.This research aimed at studying the effect of physical aspects (or what is known as dimension of tangibility) on the quality of health insurance service in the Syrian coast, And testing customers consideration for physical aspects, when they evaluate the quality of service which provide to them, and their satisfaction on the service. The researcher based on statistical questionnaire method, to collect the required data on the research problem, where the questionnaire sent to a sample of / 300 / customers of the companies involved, And then analyzing the results through the appropriate statistical programs. The results showed Low quality degrees in the service that provided by the health insurance companies in the Syrian coast For the tangibility dimension, And the physical aspects have a positive impact on the quality of this service. So that was the greatest influence for the expectations of the physical aspects, While the customers perception of these aspects have their positive effect but not sufficiently, Without having to be equal to the expectations or exceeding them. The researcher presented a set of proposals and recommendations aimed at assisting the concerned companies to better awareness and perceptions of the customers about the physical aspects that provided to them, as Keeping abreast of technical and technological development in provided service, And attention to the external and internal appearance of the company, As well as the need to adopt the quality of service by the management as a strategy for excellence and competition.